2017
DOI: 10.20961/smbr.v2i1.11678
|View full text |Cite
|
Sign up to set email alerts
|

How the Loyalty of Expedition Business Can Be Formed Through Trust and Satisfaction

Abstract: The purpose of this study is to examine the role of satisfaction and trust in mediating the relationship between service quality and brand image, and customer's intention to be loyal. The data is collected using survey and conducted by distributing questionnaire through a website. Website is selected as a media to distribute th research instrument because today marketplace shows a shift from offline to online platform. This study selected 200 people who have the intention to loyal with Jalur Nugraha Ekakurir (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to Amin, et al (2013) in their research also revealed a positive relationship between trust and loyalty. Another study by (Tabrani et al, 2018); (Wakhidah & Haryanto, 2017); and (Yildiz, 2017); also found a positive and significant influence between trust and loyalty. The higher the consumer's trust in a product/service, the higher the loyalty that will be given by the consumer to a product/service.…”
Section: Trust On Loyalty (H5 Test)mentioning
confidence: 85%
See 2 more Smart Citations
“…According to Amin, et al (2013) in their research also revealed a positive relationship between trust and loyalty. Another study by (Tabrani et al, 2018); (Wakhidah & Haryanto, 2017); and (Yildiz, 2017); also found a positive and significant influence between trust and loyalty. The higher the consumer's trust in a product/service, the higher the loyalty that will be given by the consumer to a product/service.…”
Section: Trust On Loyalty (H5 Test)mentioning
confidence: 85%
“…Rasheed & Immortal, (2014) also obtained that there is a positive relationship between Servqual and trust. Another study by (Wakhidah & Haryanto, 2017); (Yildiz, 2017); and (Uzir et al, 2021), also shows that there is a significant influence between Servqual and trust. The higher the Servqual obtained by consumers, the higher the trust that will be given by consumers.…”
Section: Servqual On Trust (H1 Test)mentioning
confidence: 91%
See 1 more Smart Citation